Effectiveness of Using the Polri Korlantas Online SIM Registration Website in SIM Services - Thamariskha, Nadya (Police Studies Review, 2024)
This research is motivated by the emergence of innovations carried out by the National Police Traffic Police in the form of using the Korlantas National Police SIM online website which aims to cut the bureaucracy of making SIMs. On the other hand, prior to the existence of the Korlantas Polri online SIM list website, the Bogor Police Traffic Satlantas had an online SIM list website named E-Satpas. But in reality, the Korlantas Polri's SIM online website which is a national program attracts no more than 3% by the Bogor people. Seeing the reality like that, then carried out research with the aim to analyze and describe the effectiveness and factors that influence the use of this website. This research was conducted at Bogor District Police with a focus on the use of the Traffic Police website. Using qualitative methods with case study techniques, primary, secondary and tertiary data sources, validity techniques with data triangulation (Moleong; 2006: 330). Data analysis is data reduction, data display, drawing and drawing conclusions. From the research conducted, it was found that the Korlantas Polri's online SIM list website has so far been constrained in the function of organizing and supplying resources, the payment system being carried out is not in accordance with the conditions agreed upon by the community. Based on the results of the study, the researchers recommend that regular training be conducted to all members of Satpas, fulfillment of budgeting, especially in the Bogor Police DIPA related to website maintenance and maintenance, fulfillment of facilities and infrastructure to support the performance of personnel in the use of the website, make improvements to the website innovation list of the Korlantas Polri online SIM so that the system is better than the Bogor Police E-Satpas, in order to improve the payment system using e-wallet, as well as to work with radio and print media to disseminate information on the Korlantas Polri online SIM list website.